Perbedaan Efektivitas Antara Larutan Madu Hutan (Apis Dorsata) Dan Larutan Madu Kelengkeng (Euphoria Longana Sp) Terhadap Pemutihan Gigi (Bleaching) - Rahmasari, Aryant Dentia; , drg. Ana Riolina, MPH; , drg. Juwita Raditya Ningsih (2014)
Bleaching is a tooth whitening method using strong oxidizing material. Strong oxidizing material which is usually used is hydrogen peroxide. Honey has glucose oxidase which has role to form hydrogen peroxide when honey dissolved in water. The average levels of hydrogen peroxide in honey is about 0.003% on average. There is difference amount of hydrogen peroxide between the monoflora's honey and the polyflora's honey. The purpose of this study is to determine difference effectivity between forest honey solution (Apis dorsata) and longan honey solution (Euphoria longana Sp) in tooth whitening (bleaching). This was a laboratory experimental study with randomized pretest-posttest controlled group design method. Using a sample of premolars post-extraction and divided into two groups. Pre-test was performed to measuretooth color before treatment. Solution of honey is prepared with a ratio of 1:1 of 60ml. Treatment were taken for 14 days, soaking for 3 hours every day and then the samples soaked in artificial saliva. On 14th day, the color intensity was measured as a post-test. The measurement results processed by the dental digital photo CIE L* a* b* analysis. Shapiro Wilk test results showed abnormal data distribution p=0.002 (p<0.05), so that the test used non-parametric Mann-Whitney and showed p=0.141 (p>0.05). These results indicating that there is no significant difference between the results of tooth whitening with forest honey (Apis dorsata) and longan honey (Euphoria Longana Sp )solution.